ANALISIS KESULITAN BELAJAR ABK (TUNA RUNGU) DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Anditiasari, Nungki (Universitas Wiralodra, 2020)
This study aims to determine the learning difficulties of students with hearing impairments in solving story problems using the role playing method and using problem solving learning according to Polya, namely: understanding problems, determining problem strategy plans, solving problem strategies, and checking the answers obtained to understand story question are seen from four aspects, namely understanding story problems, making mathematical models, computations, and drawing conclusions. The subject of this study used 2 ABK students. The data were collected by means of interviews, tests and documentations. Data analysis was carried and by drawing conclusions. Based on the results of the research students can understand story problems by applying role playing and problem solving methods, because learning becomes very fun and students can easily solve story problems. Based on the research results, students can understand story problems by applying role playing and problem solving methods, because learning becomes very fun and students can easily solve story problems. In addition, students experience some learning difficulties, namely difficulties in understanding the questions, difficulties in basic mathematical concepts, and difficulties in understanding the language that is conveyed.